Early Breast Cancer Detection Through Clinical Breast Examination Training for Midwives in Rural Jakarta, Indonesia - Indiyastutik, Sri (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45479795/Early-Breast-Cancer-Detection-Through-Clinical-Breast-Examination-Training-for-Midwives-in-Rural-Jakarta-Indonesia